The political economy of the supercars Newcastle 500 event - Patricia C. Johnson; Phoebe Everingham; Christine Everingham (Annals of Tourism Research Empirical Insights, 2023)
Public/private partnerships staging urban motor-racing events promise a range of dubious "benefits" to the host destination. These high-octane events are notorious for creating controversy over the disruptions they create. This study employs an investigative research method to explore the political economy of the Supercars Newcastle 500 in New South Wales, Australia. Results revealed how strategic misrepresentation and information asymmetry are used as tactics to avoid public scrutiny. The term "magic of major events mathematics" is coined to explain how public expenditure is "hidden" from public view, how costs are transformed into benefits, and how attendance numbers are ghosted. The research examines links between major events and touted leisure and tourism benefits as it questions the ethics of neoliberal governance practices.
Keywords: 330; Information asymmetry; Investigative research; Motor racing events; Neoliberal governance; Political economy; Public/private partnerships